Achieving organizational effectiveness of MNCs through people: Evidence from India and Mozambique - Jha, N. (2022)
Purpose – The purpose of this study is to provide human resource (HR) practitioners of multinational companies aspiring to invest in these two countries with guidelines for attaining organizational effectiveness through people. Design/methodology/approach – This study develops and tests a multiple criteria decision-making model with data collected in the banking sectors of India and Mozambique. It compares the job engagement, team building and innovation strategy preferences of Indian personnel with those of Mozambican employees. Findings – The findings of the study reveal the differences in the perceptions of the respondents of both countries regarding the importance of the strategies for organizational effectiveness. Research limitations/implications – Despite several contributions, the study has certain limitations too. Although utmost care was taken to avoid the issue of common method variance, the cross-sectional selfreported design of the study might be adversely affected by common method bias (MacKenzie and Podsakoff, 2012). Hence, future research might be conducted using different designs, such as diary studies or longitudinal studies. Future research might also be conducted making use of organizational productivity case studies to demonstrate the practicability of customizing the HR strategies using the multi-attribute decision-making approach. Practical implications – This body of work is an addition to the existing literature on cross-national studies in the field of HR management (HRM) and adds to the limited literature on HRM in the least developed countries. The study is designed to provide guidelines for the HR practitioners of multinational companies in these two countries to help them achieve enhanced organizational effectiveness. This should be of particular interest to the HR managers of the Indian companies aspiring to invest in Mozambique. Originality/value – Research in the area of HRM is mainly limited to the developed and developing nations, with very few studies centering on emerging economies. While most cross-national studies on organizational effectiveness are also largely focused on developed and developing nations, this study is unusual, in that its focus is on a fast-developing nation (India) and an emerging economy (Mozambique).